Rapid review and meta-analysis of the effectiveness of personal protective equipment for healthcare workers during the COVID-19 pandemic - Daniela Schoberer; Selvedina Osmancevic; Lea Reiter; Nina Thonhofer; Manuela Hoedl (Elsevier, 2022)
Objectives: Healthcare workers (HCWs) worldwide have and are using personal protective equipment (PPE) as COVID-19 prevention measures, including gloves, gowns, goggles, masks and hand hygiene. Although several reviews have been published on the effectiveness of PPE, these often include studies on other inflectional diseases. This is problematic, because these diseases differ with regard to, e.g. the transmissibility and viral loads in the days after infection. Therefore, we assessed the effectiveness of PPE to protect HCWs from COVID-19 infections. Design: Rapid review of literature. Methods: We followed a practical guide to conduct the rapid review based on a protocol established by the Cochrane Rapid Reviews Methods Group. Meta-analyses have been conducted to synthesize the results. The confidence in the evidence was determined using the GRADE method. Results: We found 461 reviews and 208 primary studies, of which 16 systematic reviews included 11 observational studies of interest. Wearing PPE conferred significant protection against infection with COVID-19 as opposed to not wearing adequate PPE. Overall, the review results show that wearing face masks can significantly protect HCWs from infection. We found no effects for wearing gloves and gowns. Practicing thorough hand hygiene and having proper PPE, as compared to lacking proper PPE, showed a protective but not statistically significant effect. No studies reported the side effects of wearing PPE or acceptance rates. Conclusion: This evidence supports PPE use by HCW, and especially N95 masks, to reduce the risk of a COVID-19 infection.